Makna Sakinah dan Tuma’ninah dalam Al Qur’an (Kajian Semantik Toshihiko Izutsu) - Maghfiroh, Maghfiroh; Faisol, Faisol; Al Anshory, Abdul Muntaqim (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to reveal the meaning of sakinah and tuma'ninah in the Qur'an through Thosihiko Izutsu's semantic approach. Sakinah is often interpreted as the calmness that Allah bestows on believers in stressful situations, while tuma'ninah refers to the tranquility of the heart that comes from strong belief and faith. Although the two seem similar, analysis shows that sakinah is more related to external and situational contexts, while tuma'ninah focuses on internal and spiritual tranquility. The research utilizes primary sources such as the Qur'an and various classical and modern tafsir to provide an in-depth and contextualized understanding of these two terms. The results confirm that understanding the differences and similarities between sakinah and tuma'ninah is crucial for Muslims in achieving true peace of mind. The findings contribute significantly to the field of Islamic studies and semantics, and offer practical guidance for achieving peace of mind in daily life.